Interactive Data Extraction Analysis (IDEA): The Determinants of Behavioral Intention among Field Audit Officers in Putrajaya State Director Office, IRBM - Abdul Aziz, Saliza; Isa, Islahudin (2017)
The introduction of new technology by organization is to improve their employee productivity and performance in their jobs. The introduction of Interactive Data Extraction Analysis (IDEA) tool by Inland Revenue Board of Malaysia (IRBM) is to boost the productivity among field audit officers. However, low acceptance level in the tool has led to phenomena of productivity paradox among the auditors. This study is trying to examine employee behavioral intention on new technology implemented in the workplace. This study is considered as new in Malaysia because limited study has been done to investigate employee behavioral intention and acceptance of this new technology. The Technology Acceptance Model (TAM) introduced by Davis (4989) is the fundamental theory adopted in this study to determine the relationship and via a survey method, 123 completed questionnaires have been collected from three branches under Putrajaya State Director Off~ce comprises of KL Bandar, Chetas and Wangsa Maju branches. The Statistical Package for Social Science (SPSS) is utilized to perform the descriptive analysis, validity test, reliability test and regression analysis on the five hypothesized relationship. The result indicated that perceived usefulness is the most critical factor that influences the user intention and acceptance. The result of this study recommended that more intention on increase user ease of use through conducting more intension twining and enhance the current. technological facilities.